CREATING HYBRID URBAN SPACES FOR CHILDREN: PLAY STREETS OF ISTANBUL - Kara, N.; Sungur, A. (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2019)
We live in an age where learning is not limited to educational buildings. Museums, parks, sports clubs, public spaces and the city itself are considered as a learning environment and urban space; as a tool for learning. For children who are born and raised in cities, urban landscape is their natural environment. However, children's interaction with cities and urban environment is limited. Physical and social barriers like dominance of traffic, physical security, stranger danger, fear of crime are barriers to discover and learn about the environment the children live in. Playing is an important tool for children to engage with their environment, interact, socialize, discover and learn. Many countries accept the role of play in children's physical, cognitive and emotional development as a matter of public health. Cities are in need of allocating spaces for children to play and playability is one of the main subjects discussed on becoming a livable and sustainable city. Playgrounds and school grounds are immediate safe places where children can play. But they do not offer an urban experience as they are not a part of the daily life of the urban community as a whole. A hybrid formation of these isolated and safe play spaces and wild urban spaces called Play Street or Child Street are emerging in Turkey, as in some other countries in Child Friendly Cities Initiative Network of UNESCO. Started in housing areas, many child friendly hybrid streets spread close to, or even attached to school areas; creating a buffer zone between the school and the city where traffic is blocked with hopes of welcoming and encouraging to play outside. This study explores the planning and design of the Play Streets/ Child Streets of Istanbul and patterns of use by urban dwellers and their potentials of becoming an outdoor learning space; while discussing its positive and negative effects to the children, community and urban environment.
Keywords: Outdoor learning; play; child friendly city; play street; child street; school ground; Istanbul; Education & Educational Research; Psychology